ANALYSIS OF EXISTING AND INDICATIONS AREA OF THE PANEMBONG LAKE, SERANG REGENCY, BANTEN PROVINCE - Isvan Taufik; Meysa Cahya Gemilang; Endang Sudrajat (Department of Geodesy Engineering, Faculty of Engineering, Diponegoro University,Indonesia, 2026)
Indonesia is estimated to have more than 1,575 lakes, consisting of 840 large lakes and 735 small lakes (situ). As a source of raw water and flood control, lakes and reservoirs play a crucial role in maintaining the balance of land use and natural resources. This study will analyze the existing conditions and area indications of Situ Panembong by doing a Mapping/Topographic Surveying This study is expected to provide important contributions to the mapping and discourse on lakes in Indonesia, as well as information for maintaining Situ Panembong in Banten Province as a protected area. A key benefit of mapping the survey data in this study is that it can also summarize information from the field, allowing it to be used in planning. The method used in this research employs qualitative analysis. The technical measurement methods used in this activity include measuring land areas, topography, situation, longitudinal and transverse profiles, and aerial photography. The reasult is that Conditions in the Panembong Lake demonstrate a strong relationship between hydrology, land use, and socio-economic and industrial activities. Aerial mapping using digital photogrammetry technology produced several key products—orthophotos, DSMs, DTMs/topography, and 3D models. These results collectively provide an accurate spatial representation of the morphological conditions and physical characteristics of Panembong kae. The Digital Surface Model (DSM) shows elevation variations that encompass all surface features, including vegetation and anthropogenic structures. The extracted Digital Terrain Model (DTM) and topographic maps show a relatively gentle contour across the lake body, with a gradual increase in elevation toward the perimeter. These topographic characteristics confirm that the lake is located in a natural basin with a flow pattern that vegetates toward the center of the reservoir.